EFEKTIVITAS PEMANFAATAN FREE WEBLOG SEBAGAI CLASSROOM BLOGGING BERBASIS WEB DI JURUSAN TEKNIK ELEKTRO UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Sartono, Sri; Harlanu, M.; Suryanto, Agus (Jurnal Penelitian Pendidikan, 2012)
One appropriate learning strategies to support e-learning, is a learning method Student Centered Learning (SCL). The term Student Centered Learning (SCL) is a method of learning and teaching in education wherein the student has responsibility for several critical activities such as planning, learning, interaction between faculty and students, research and evaluation of the learning that has been done. This research is a class action (class room action research), which refers to the process model, described by Kemmis and Mc Taggart. This study developed two forms dalarn, including the cycle of planning, action, observation and reflection. The results showed that, first; Model blogging webbased classroom learning by presenting web directly or to develop creative thinking skills have good prospects to be used in similar courses with courses in multimedia systems, second; blogging classroom learning model web-based to improve student achievement as much as 80% of students scored at least 70, Third Model classroom blogging web-based learning can also increase the ability to think creatively, as much as 70% of students have a high level of creativity to the criteria.